Towards successful improvement of students’ residential management processes using the enterprise architecture maturity model - Moses, Golooba; Musleh, Mahmoud M; Nofal, Karama M A; Hassan, Azizah; Monther, Khansa; Ahlan, Abdul Rahman (WCSIT, 2012)
In this information age many institutions have resorted to using information systems to handle most of the business processes. However, well as many of them spend huge resources on implementing information systems to solve their problems, many times the value for money invested in putting up these information systems is not optimally realized because more often these systems fail to fully address the problems they were intended to solve. This article examines how organization such as a University, can use both e-management and LEAN management principles to improve their business processes and the overall enterprise architecture; with an aim of improving the business process at the University through redesigning the current enterprise architecture based on Service oriented Architecture (SOA). It is hoped that the redesigned enterprise architecture knitted around the above principles will go a long way in improving the satisfaction levels on the side of students, and other stakeholders like staff and senior management, reduce on wastage, improve on agility of business processes, increase productivity on the side of employees and thus result into happy managers and students. The methodology was qualitative which involved conducting indepth interviews with students and senior managers from business process owners’ side, data owners and senior managers at the Information Technology Division of the University. The following findings and recommendations were based on a single case study conducted at University X where students are not satisfied with the current quality of service they receive from the University’s hostel management.